Synthesis of Polybenzoxazine as an environmentally friendly adhesive material from cardanol and post-consumer PET source - Luong, Viet Chat; Huynh, Khanh Tuong; Du Ngoc, Uy Lan; Cao, Xuan Viet (Vietnam Journal of Science and Technology, 2024)
In this study, a thermosetting benzoxazine was successfully prepared from environmentally friendly sources to be used as an adhesive. The phenolic component used for the synthesis of the benzoxazine monomer is cardanol derived from the cashew nutshell, while the amine fractions are terephthalamide, which is a product of the amination process of used polyethylene terephthalate plastic bottles (PET). The structure of the benzoxazine monomer was determined by FT-IR and 1H-NMR spectroscopy. The thermal and curing behavior of the materials was investigated by differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). A lap-shear adhesion testing (ASTM D1002-10) was performed to measure the bond strength of the material to the CT3 steel surface. The adhesive properties with a shear strength of 7.29 MPa are excellent compared to other commercial adhesives. This result indicates the great potential of this benzoxazine for adhesive applications in practice.